2016
DOI: 10.1016/j.apcatb.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Boron doped BiOBr nanosheets with enhanced photocatalytic inactivation of Escherichia coli

Abstract: Boron (B) doped bismuth oxybromide (B-BiOBr) nanosheets were synthesized using a hydrothermal method and their photocatalytic activities were investigated through inactivating a typical bacterium, Escherichia coli K-12 using fluorescence tubes as visible light (VL) sources. B atoms are successfully doped into the crystal lattice of BiOBr. However, the morphology, crystal structure, and {001}-facet exposed feature of B-BiOBr nanosheets remain unchanged compared with pure BiOBr nanosheets. Significantly, the as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(69 citation statements)
references
References 49 publications
6
63
0
Order By: Relevance
“…The CBs values are found to be 0.126 V and À0.69 V for BiOCl and BiOBr, respectively. 33,39 Correspondingly, the VB values for BiOCl and BiOBr are calculated to be 3.61 and 2.06 eV according to their band gap energy (E g ) values. The values determined in this study are similar to those reported in previous literature.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…The CBs values are found to be 0.126 V and À0.69 V for BiOCl and BiOBr, respectively. 33,39 Correspondingly, the VB values for BiOCl and BiOBr are calculated to be 3.61 and 2.06 eV according to their band gap energy (E g ) values. The values determined in this study are similar to those reported in previous literature.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…One way to remediate these problems is by doping or preparing composites materials. For example, boron doped BiOBr nanosheets were shown to inactivate E. coli K-12 using fluorescence tubes as visible light source [54]. In another report, BiOBr was combined with other semiconductors (such as CeO 2 , WO 3 , CaFe 2 O 4 ) to form heterojunctions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Boron-doped BiOBr (B-BiOBr) was synthesized by adding H 3 BO 3 in the precursors of BiOBr before hydrothermal treatment. 110 The B-BiOBr with a B/Bi molar ratio of 0.75% performed excellently with a stable VLD inactivation efficiency, with 7-log E. coli cells inactivated within 30 min in all three cycles. What's more, the BiOBr of 2D morphology exhibited an interesting self-doping behavior by a post-treatment under light irradiation.…”
Section: D Metal Oxyhalide Photocatalysts For Photocatalytic Disinfementioning
confidence: 88%
“…After that, a series of exogenously doped and self‐doped photocatalysts were fabricated with the BiOBr nanosheets with a high percentage of {001} facets. Boron‐doped BiOBr (B‐BiOBr) was synthesized by adding H 3 BO 3 in the precursors of BiOBr before hydrothermal treatment . The B‐BiOBr with a B/Bi molar ratio of 0.75% performed excellently with a stable VLD inactivation efficiency, with 7‐log E. coli cells inactivated within 30 min in all three cycles.…”
Section: D Metal Oxyhalide Photocatalysts For Photocatalytic Disinfementioning
confidence: 99%